Is Congestion Pricing Effective for Traffic Jams? - Ayrat, Elzat; Lin, Xiaoyan (Promet - Traffic&Transportation, 2022)
The complexity of urban congestion requires policy-makers to adopt different congestion control measures that suit the characteristics of the city at the proper time. The paper focuses on the most controversial congestion pricing and offers methods to judge the efficacy of the policy by game theoretic approaches. It is found that congestion pricing is not merely a Pigouvian tax that internalizes drivers’ externalities, but also a powerful means to enhance public traffic proportion and balance road utilization on the premise of maximized social util-ity. Meanwhile, the embedded multiple case study shows that theoretical correctness of the policy is a necessary, but not sufficient condition for its effectiveness because the valid operation of the policy further requires cities to hold certain attributes in some aspects, such as econom-ic level, population density, proper pricing mechanism, and the ability to limit access to and from certain areas. Moreover, the authority should pay attention to matching the policy goal and its functions for successful implementation.